The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1103/physreve.91.033204
|View full text |Cite
|
Sign up to set email alerts
|

Circular polarization memory in polydisperse scattering media

Abstract: We investigate the survival of circularly polarized light in random scattering media. The surprising persistence of this form of polarization has a known dependence on the size and refractive index of scattering particles, however a general description regarding polydisperse media is lacking. Through analysis of Mie theory, we present a means of calculating the magnitude of circular polarization memory in complex media, with total generality in the distribution of particle sizes and refractive indices. Quantif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…A known exception with linear depolarization larger than circular depolarization is blood, since red blood cells are anuclear and do not have abundant organelles [93]. Overall, the comparison of tissue linear and circular depolarization can provide interesting information about scatterers (e. g. scatterer sizes) which might produce more applications in the future [89,97]. Different depolarization mechanisms for linearly and circularly polarized light also result in the non-depolarized backscattered linearly and circularly polarized light probing different tissue volumes, allowing depth resolved imaging of isotropic tissue by adjusting the ellipticity of the incident polarization [9,98].…”
Section: Polarized Light and Biological Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…A known exception with linear depolarization larger than circular depolarization is blood, since red blood cells are anuclear and do not have abundant organelles [93]. Overall, the comparison of tissue linear and circular depolarization can provide interesting information about scatterers (e. g. scatterer sizes) which might produce more applications in the future [89,97]. Different depolarization mechanisms for linearly and circularly polarized light also result in the non-depolarized backscattered linearly and circularly polarized light probing different tissue volumes, allowing depth resolved imaging of isotropic tissue by adjusting the ellipticity of the incident polarization [9,98].…”
Section: Polarized Light and Biological Tissuementioning
confidence: 99%
“…Circular depolarization is caused by the propagation direction of circularly polarized light and the randomization of its helicity [88]. It has been found that in a suspension of spherical scatterers linear depolarization is lower than circular depolarization for small spheres (Rayleigh scatterers), and also for large spheres with relative refractive index close to 1 (following Rayleigh-Gans approximation or the first Born approximation, known as optically "soft" or "tenuous" [43]), whereas the reverse is true for large spheres with relative refractive 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 index much larger than 1 (Mie scatterers) [14,[87][88][89][90][91][92]. It was also reported that linearly polarized light is better preserved through longer propagation distances than circularly polarized light in most biological tissues including fat, tendon, artery, myocardium, colon, bladder [14,16,17,20,[93][94][95] due to the significant contribution from relatively low refractive index large scatterers like cell nuclei and presence of Rayleigh scatterers including various cell organelles and other biological particles [14,96].…”
Section: Polarized Light and Biological Tissuementioning
confidence: 99%
“…[1][2][3][4][5][6][7]. This report describes how optical images acquired using linearly polarized light can specify the anisotropy of scattering (g) and the ratio of reduced scattering ½μ 0 s ¼ μ s ð1 − gÞ to absorption (μ a ), i.e., N 0 ¼ μ 0 s ∕μ a .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we explore the feasibility of such system that is based on the property of circular polarized light to maintain its polarization in highly scattering media at larger depths as compared to linearly polarized light due to the so called circular "polarization memory" effect [34,35] Circularly polarized light undergos small-angle, forward scattering events in diffusely scattering media with Mie scatterers that are characterized by a predominately forward scattering phase function that largely preserves helicity for long distances in a turbid medium [22,34,36]. Furthermore, it was recently demonstrated that elliptically polarized light can be used to image scattering phantoms and biological tissue at different depths by varying the degree of ellipticity from linear to circular polarization [37].…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative method, our group and others have developed a simple linear polarization gating to isolate tissue signals originating from shallow depths in tissues from the diffuse background of the underlying stroma using spectroscopic and imaging setups [13][14][15][16][17][18][19][20][21]. In polarization gated spectroscopy and imaging, polarized photons maintain their incident polarization for a particular number of mean free paths (MFP) depending on density of optical scatterers and their properties such as anisotropy factor [22,23]. In linear polarization gating, a sample is illuminated with a linear polarized light and two components of the scattered light are detected: the co-polarized signal with its polarizations parallel to the incident polarization (I ║ ) and the cross-polarized signal with its polarization orthogonal to the incident light (I^).…”
Section: Introductionmentioning
confidence: 99%